Yoga training enhances elastic biomechanics of trapezius and hamstrings: a quantitative SWE assessment - Liu, Jing; Yang, Lin (Frontiers in Physiology, 2026)
AimTo investigate the association between long-term Yoga practice and changes in trapezius and hamstring biomechanics using shear-wave elastography (SWE), and to identify reliable measurement conditions.MethodsEighty-one healthy women were assigned to a Yoga group (n = 51) or non-Yoga control group (n = 30). The mean Young’s modulus (Emean) of the trapezius, biceps femoris long head, and semitendinosus was assessed at baseline, 1, 3, and 6 months under standardized postures (neutral, flexed, extended, and 90° knee flexion) and imaging planes (transverse/longitudinal) using a Siemens ACUSON Redwood system.ResultsEighty-one healthy adult women were enrolled (Yoga: n = 51; non-Yoga: n = 30), with no significant baseline differences between groups (all p > 0.05). Muscle thickness did not differ between groups at any time point for any muscle (all p > 0.05). For the trapezius, significant main effects of position (p < 0.001) and time (p = 0.014), as well as a significant group × time interaction (p < 0.001), were observed, with a progressive reduction in Emean in the Yoga group only. In the hamstring muscles, significant group × time interactions were detected for both the biceps femoris long head (longitudinal: F (2.66, 210.24) = 12.11, p < 0.001; transverse: F (2.42, 191.04) = 9.19, p < 0.001) and the semitendinosus (longitudinal: F (2.05, 161.87) = 9.93, p < 0.001; transverse: F (2.47, 195.00) = 5.21, p = 0.002). Longitudinal measurements consistently showed greater sensitivity to temporal changes than transverse measurements, and weak inverse correlations were observed between cumulative yoga training duration and muscle elasticity (all p < 0.05).ConclusionSix months of regular Yoga was associated with improved muscle elasticity, while SWE provides a robust and quantitative assessment of posture-dependent biomechanical adaptations.